Localization and translocation of RhoA protein in the human gastric cancer cell line SGC-7901 - Tao, Yan (The WJG Press and Baishideng, 2008)
AIM: To elucidate the localization of RhoA in gastric SGC-7901 cancer cells and its translocation by lysophosphatidic acid (LPA) and/or 8-chlorophenylthio-cAMP (CPT-cAMP). METHODS: Immunofluorescence microscopy was used to determine the localization of RhoA. Western blotting was used to detect both endogenous and exogenous RhoA in different cellular compartments (membrane, cytosol, nucleus) and the translocation of RhoA following treatment with LPA, CPT-cAMP, or CPT-cAMP + LPA. RESULTS: Immunofluorescence staining revealed endogenous RhoA to be localized in the membrane, the cytosol, and the nucleus, and its precise localization within the nucleus to be the nucleolus. Western blotting identified both endogenous and exogenous RhoA within different cellular compartments (membrane, cytosol, nucleus, nucleolus). After stimulation with LPA, the amount of RhoA within membrane and nuclear extracts increased, while it decreased in the cytosol fractions. After treatment with CPT-cAMP the amount of RhoA within the membrane and the nuclear extracts decreased, while it increased within the cytosol fraction. Treatment with a combination of both substances led to a decrease in RhoA in the membrane and the nucleus but to an increase in the cytosol. CONCLUSION: In SGC-7901 cells RhoA was found to be localized within the membrane, the cytosol, and the nucleus. Within the nucleus its precise localization could be demonstrated to be the nucleolus. Stimulation with LPA caused a translocation of RhoA from the cytosol towards the membrane and the nucleus; treatment with CPT-cAMP caused the opposite effect. Furthermore, pre-treatment with CPT-cAMP was found to block the effect of LPA.